N-acetyl-seryl-aspartyl-lysyl-proline: a valuable endogenous anti-fibrotic peptide for combating kidney fibrosis in diabetes - Kanasaki, Keizo; Nagai, Takako; Nitta, Kyoko; Kitada, Munehiro; Koya, Daisuke (Frontiers in Pharmacology, 2014)
Fibroproliferative diseases are responsible for 45% of deaths in the developed world. Curing organ fibrosis is essential for fibroproliferative diseases. Diabetic nephropathy is a common fibroproliferative disease of the kidney and is associated with multiorgan dysfunction. However, therapy to combat diabetic nephropathy has not yet been established. In this review, we discuss the novel therapeutic possibilities for kidney fibrosis in diabetes focusing on the endogenous anti-fibrotic peptide, N-acetyl-seryl-aspartyl-lysyl-proline (AcSDKP), which is the substrate for angiotensin-converting enzyme and exhibits meaningful anti-fibrotic effects in various experimental models of fibrotic disease.